2016
DOI: 10.1016/j.jagp.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Risk Factors and Brain Positron Emission Tomography Measures of Amyloid and Tau in Nondemented Adults with Memory Complaints

Abstract: Objective Exercise and diet impact body composition, but their age-related brain effects are unclear at the molecular imaging level. To address these issues, we determined whether body mass index (BMI), physical activity, and diet relate to brain positron emission tomography (PET) of amyloid plaques and tau tangles using 2-(1-(6-[(2-[F-18]fluoroethyl)(methyl)amino]-2-naphthyl)ethylidene)malononitrile (FDDNP). Methods Volunteers (n = 44, mean age = 62.6 ± 10.7 years) with subjective memory impairment (n = 24)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 41 publications
4
33
0
1
Order By: Relevance
“…A small, multi-modal study in cognitively normal, middle-aged adults found increased beta-amyloid plaque burden and decreased glucose metabolism in those who adhered to the MD [64]. Similar results were found in a study examining amyloid and tau pathology through PET imaging in older adults with subjective memory complaints and MCI; in this study, greater adherence to the MD was associated with less pathology in both groups [65]. If results can be replicated in larger samples, these data may support using PET imaging markers as outcome measures in clinical trials.…”
Section: Pet Imaging Studiessupporting
confidence: 84%
“…A small, multi-modal study in cognitively normal, middle-aged adults found increased beta-amyloid plaque burden and decreased glucose metabolism in those who adhered to the MD [64]. Similar results were found in a study examining amyloid and tau pathology through PET imaging in older adults with subjective memory complaints and MCI; in this study, greater adherence to the MD was associated with less pathology in both groups [65]. If results can be replicated in larger samples, these data may support using PET imaging markers as outcome measures in clinical trials.…”
Section: Pet Imaging Studiessupporting
confidence: 84%
“…The results showed that lower Aβ burden was found in subjects more engaged in cognitively stimulating activities, particularly during early and middle life. A recent study suggests that greater levels of physical activity in MCI subjects is associated with lower Aβ plaque and tangle deposition, estimated by PET67. Thus, there seems to be a correlation between cognitive/physical activity and Aβ burden.…”
Section: Discussionmentioning
confidence: 98%
“…A recent cross-sectional study of individuals with MCI or subjective memory impairment ( N = 44) reported a relationship between greater frequency of following a Mediterranean-type diet and less brain Aβ/tau burden as assessed by 2-(1-(6-[(2-[F-18]fluoroethyl)(methyl)amino]-2-naphthyl)ethylidene)malononitrile ( 18 F-FDDNP); a pan-amyloid PET tracer that binds to both Aβ plaques and tau deposits. Unfortunately, however, the lack of selectivity of the tracer makes it impossible to determine whether the diet was associated with Aβ, tau, or a combination of both 21 . To-date, only one study has specifically examined the relationship between MeDi adherence and cerebral Aβ load.…”
Section: Discussionmentioning
confidence: 99%